Optimizing the Role of the Committee through the Parents Association in Supporting and Realizing the Quality of Education at SDN 06 Metro Utara - Tusriyanto Tusriyanto; Lina Novita (Universitas Pakuan, 2022)
The purpose of this study was to describe the role of the committee through the parents' association in supporting the quality of education at SDN 06 Metro Utara. This study is a qualitative descriptive study by examining all available data from various sources, namely from interviews with both the principal and committee administrators, observations were made to obtain a comprehensive picture related to the condition of SDN 06 Metro, as well as using field notes, personal documents, documents official, still images to support the main data. Based on the results of the study, it was obtained data that the committee of SDN 06 Metro Utara has carried out its role well through the parents' association in supporting and realizing the quality of education as evidenced by the increase in accreditation from